Pharmaceutical cost savings from the treatment of oncology patients in clinical trials - Borja Gómez Mediavilla; Paloma Lanza-León; Virginia Martínez Callejo; David Cantarero-Prieto; María Lanza Postigo; Matilde Salcedo Lambea; Yolanda Blanco Mesonero; María Ochagavia Sufrategui; Ignacio Durán; Carmen María Sarabia Cobo (Biomedical Journal)
Objective: The aim of this study was twofold: to assess the annual pharmaceutical savings associated with the treatment of cancer patients at Marqués de Valdecilla University Hospital and to estimate the cost of innovative antineoplastic therapies that patients receive as experimental treatment, both during clinical trials throughout 2020. Material and methods: An observational and financial analysis of the drug cost related to clinical trials was applied. Direct cost savings to the Regional Health System of Cantabria and the cost of innovative therapies used as an experimental treatment in clinical trials were quantified. Results: This study includes 38 clinical trials with a sample of 101 patients. The clinical trials analyzed provide a total cost savings of €603,350.21 and an average cost saving of €6630.22 per patient. Furthermore, the total investment amounts to €789,892.67, with an average investment of €15,488.09 per patient. Conclusions: Clinical trials are essential for the advancement of science. Furthermore, clinical trials can be a significant source of income for both hospitals and Regional Health Systems, contributing to their financial sustainability.